Ultra-white glass and preparation method thereof
Through specific raw material ratios and process steps, the bubble removal problem in ultra-white glass is solved, and the preparation of ultra-white glass with high transparency and excellent optical properties is achieved, which improves the chemical and mechanical properties of the glass.
Patent Information
- Application Number
- CN202510283516.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-03-11
AI Technical Summary
During the preparation of existing ultra-white glass, it is difficult to effectively remove air bubbles in the glass, resulting in the impact of the transparency and optical properties of the glass.
Ultra-white glass preparation methods using specific raw material ratios include quartz sand, sodium carbonate, boronite, magnesium sand, calcined alumina, potassium oxide, zinc oxide and phosphorus pentoxide, and through process steps such as kiln melting, vacuum debubbing, calendering molding and annealing treatment, combined with strontium chloride, calcium fluoride, barium nitrate and zirconium oxide as clarification decolorizers, synergistically to remove bubbles.
The high transparency and excellent optical properties of ultra-white glass are achieved, which improves the chemical stability, mechanical strength and compressive strength of the glass, while reducing the thermal expansion coefficient and melting temperature of the glass.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glass preparation, and specifically relates to ultra-white glass and a preparation method thereof. Background Art
[0002] Ultra-clear glass is a kind of ultra-transparent low-iron glass, also known as low-iron glass and high-transparency glass. It is a high-quality, multifunctional new high-end glass variety with a light transmittance of more than 91.5%. It has the characteristics of crystal clearness, high-end elegance, and is known as the "Crystal Prince" of the glass family.
[0003] Ultra-clear glass has all the processing properties of high-quality float glass, and has excellent physical, mechanical and optical properties. It can be processed in various ways like other high-quality float glass. The incomparable superior quality and product performance make ultra-clear glass have a broad application space and bright market prospects, but ultra-clear glass is difficult to process and prepare.
[0004] One of the important factors in glass quality is the bubbles in the glass. Glass is made by mixing raw materials such as silica sand, soda ash, quartz stone, etc., and then melting them at high temperature. The glass melted at high temperature is a high-viscosity liquid containing a large number of bubbles. When no clarifier is used, the bubbles contain the most carbon dioxide and nitrogen, which cannot be dissolved in the molten glass. If it simply relies on the bubbles rising to the surface of the glass and then bursting and releasing, it will take a lot of time and does not meet the requirements of industrial production.
[0005] Therefore, it is necessary to add clarifying and decolorizing agents during the preparation of ultra-white glass. Currently, the most commonly used clarifying and decolorizing agents include Sb 2 O 5 , Sb 2 O 3 and CuSO 4 etc., among which Sb 2 O 5 and Sb 2 O 3 During the glass melting process, CuSO4 may react with other components in the glass, affecting the properties of the glass. 4 The use of clarifiers will cause glass emulsification, that is, opaque milky white spots will appear on the glass surface, affecting the transparency and optical properties of the glass. Therefore, the existing glass clarification and decolorization agents still need to be improved in terms of improving the transmittance of ultra-white glass and eliminating bubbles. Summary of the invention
[0006] The purpose of the present invention is to provide an ultra-white glass, which has good whiteness and visible light transmittance; the present invention also provides a preparation method thereof.
[0007] The ultra-white glass of the present invention is composed of the following raw materials, measured by weight: 110 parts of quartz sand, 18-20 parts of sodium carbonate, 14-16 parts of colemanite, 4.5-5.5 parts of magnesia, 2.6-2.8 parts of calcined aluminum oxide, 1.1-1.3 parts of potassium oxide, 0.8-1.0 parts of zinc oxide, 1.5-1.7 parts of phosphorus pentoxide, 0.15-0.20 parts of strontium chloride, 0.3-0.34 parts of calcium fluoride, 0.25-0.27 parts of barium nitrate and 0.16-0.18 parts of zirconium oxide.
[0008] in:
[0009] The chemical composition of the quartz sand is as follows in terms of mass percentage: SiO 2 99.57%,Al 2 O 3 0.21%, Fe 2 O 3 0.0075% and loss on ignition is 0.2125%.
[0010] The chemical composition of the magnesia is as follows, in terms of mass percentage: MgO 97.85%, CaO 0.82%, SiO 2 0.43%, Fe 2 O 3 0.37%,Al 2 O 3 0.38% and loss on ignition is 0.15%.
[0011] The chemical composition of the calcined alumina is as follows, in terms of mass percentage: Al 2 O 3 99.72%, Na 2 O0.20%, loss on ignition is 0.08%.
[0012] The method for preparing ultra-white glass of the present invention comprises the following steps:
[0013] (1) Add quartz sand, sodium carbonate, colemanite, magnesia, calcined alumina, potassium oxide, zinc oxide and phosphorus pentoxide into a kiln for melting, vacuum and degas for 8-10 minutes, then add strontium chloride, calcium fluoride, barium nitrate and zirconium oxide when the temperature is raised to 580-600°C, continue to raise the temperature to 1530-1550°C and keep the temperature for 8.2-8.3 hours to obtain glass liquid;
[0014] (2) The glass liquid is fed into a calender for calendering;
[0015] (3) The formed glass is annealed in an annealing kiln to produce ultra-white glass.
[0016] in:
[0017] The temperature of the calendering process in step (2) is 1150-1180°C.
[0018] The annealing treatment in step (3) is to first cool the temperature to 520-530°C at a rate of 3.8-4.0°C / min and keep it at that temperature for 30-40 minutes, then cool the temperature to 320-330°C at a rate of 2.5-2.8°C / min, and finally cool naturally to room temperature.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The ultra-white glass of the present invention mainly comprises quartz sand, sodium carbonate, colemanite, magnesia, calcined alumina and potassium oxide, and zinc oxide and phosphorus pentoxide are added. The introduction of alumina by calcined alumina reduces the expansion coefficient of the glass, thereby improving the chemical stability and mechanical strength of the glass. The introduction of magnesium oxide by magnesia reduces the crystallization tendency and hardening speed of the glass, thereby improving the forming properties of the glass. The introduction of sodium oxide by sodium carbonate can greatly reduce the viscosity of the glass liquid. In addition, K 2 O can increase the transparency and gloss of glass. Calcium oxide and boron trioxide are introduced through colemanite. Calcium oxide can promote the formation of silicate structure in glass, increase the density and hardness of glass, while boron trioxide forms a strong network in the glass structure, improving the hardness and compressive strength of glass. When zinc oxide is added to glass as a network modifier, it can improve the chemical stability of glass while reducing the melting temperature of glass. In addition, it can reduce the thermal expansion coefficient of glass, enhance the deformation resistance of glass and increase the whiteness of glass; phosphorus pentoxide can enhance the light transmittance of glass in the ultraviolet region, and can also improve the dispersion coefficient of glass. Therefore, the interaction between the raw materials ensures the stability and transmittance of ultra-white glass.
[0021] (2) The ultra-white glass of the present invention uses a mixture of strontium chloride, calcium fluoride, barium nitrate and zirconium oxide as a clarifying and decolorizing agent, and the four have a synergistic effect. Among them, strontium chloride is decomposed by heat during the glass melting process to produce chlorine and other gases. The fluoride ions produced by the decomposition of calcium fluoride can react with SiO2 in the glass. 2Reaction to generate volatile fluorides, thereby reducing the viscosity of the glass melt. These gases form tiny bubbles in the glass melt, which rise by buoyancy and carry other gases out, thereby reducing the bubbles in the glass. Barium nitrate decomposes to produce oxygen, nitric oxide and nitrogen dioxide during the glass melting process, improving the clarification effect. Strontium chloride, calcium fluoride and barium nitrate decompose to produce different types of gases and release gases at different temperatures. The temperature at which the three decompose to produce gases covers the entire process of glass melting, including the glass liquid formation process and the glass liquid clarification process. In addition, due to the different and diverse types of gases formed, it is beneficial to increase the partial pressure of the lower partial pressure gas in the original bubble, promote the precipitation of other component gases dissolved in the glass liquid into the bubble, so that the bubble grows and precipitates. Zirconia has good chemical stability and can remain stable in the glass melt, significantly reducing the viscosity of the glass melt, making it easier for bubbles to merge and float, thereby accelerating the clarification process. In addition, the addition of zirconium oxide can significantly increase the refractive index of the glass and reduce dispersion, thereby improving the optical properties of the glass.
[0022] (3) The method for preparing the ultra-white glass of the present invention has a simple process and easy-to-control parameters. The prepared ultra-white glass has excellent whiteness and visible light transmittance. DETAILED DESCRIPTION
[0023] The present invention is further described below with reference to the embodiments.
[0024] Example 1
[0025] The ultra-white glass described in this embodiment 1 is composed of the following raw materials, measured by weight: 110 parts of quartz sand, 19 parts of sodium carbonate, 15 parts of colemanite, 5.0 parts of magnesia, 2.7 parts of calcined alumina, 1.2 parts of potassium oxide, 0.9 parts of zinc oxide, 1.6 parts of phosphorus pentoxide, 0.18 parts of strontium chloride, 0.32 parts of calcium fluoride, 0.26 parts of barium nitrate, and 0.17 parts of zirconium oxide.
[0026] in:
[0027] The chemical composition of the quartz sand is as follows in terms of mass percentage: SiO 2 99.57%,Al 2 O 3 0.21%, Fe 2 O 3 0.0075% and loss on ignition is 0.2125%.
[0028] The chemical composition of the magnesia is as follows, in terms of mass percentage: MgO 97.85%, CaO 0.82%, SiO 2 0.43%, Fe 2 O 3 0.37%,Al2 O 3 0.38% and loss on ignition is 0.15%.
[0029] The chemical composition of the calcined alumina is as follows, in terms of mass percentage: Al 2 O 3 99.72%, Na 2 O0.20%, loss on ignition is 0.08%.
[0030] The method for preparing the ultra-white glass described in this embodiment 1 comprises the following steps:
[0031] (1) Add quartz sand, sodium carbonate, colemanite, magnesia, calcined alumina, potassium oxide, zinc oxide and phosphorus pentoxide into a kiln for melting, vacuumize and degas for 9 minutes, then add strontium chloride, calcium fluoride, barium nitrate and zirconium oxide when the temperature reaches 590°C, continue to heat to 1540°C and keep the temperature for 8.25 hours to obtain glass liquid;
[0032] (2) The glass liquid is fed into a calender for calendering;
[0033] (3) The formed glass is annealed in an annealing kiln to produce ultra-white glass.
[0034] in:
[0035] The temperature of the calendering process in step (2) is 1165°C.
[0036] The annealing treatment in step (3) is to first cool the temperature to 525°C at a rate of 3.9°C / min and keep the temperature for 35 minutes, then cool the temperature to 325°C at a rate of 2.6°C / min, and finally cool naturally to room temperature. The whiteness of the ultra-white glass prepared in Example 1 is 0.061F, and the visible light transmittance is 96.1%.
[0037] Example 2
[0038] The ultra-white glass described in this Example 2 is composed of the following raw materials, in parts by weight: 110 parts of quartz sand, 20 parts of sodium carbonate, 14 parts of colemanite, 4.5 parts of magnesia, 2.8 parts of calcined alumina, 1.1 parts of potassium oxide, 1.0 parts of zinc oxide, 1.7 parts of phosphorus pentoxide, 0.15 parts of strontium chloride, 0.34 parts of calcium fluoride, 0.27 parts of barium nitrate, and 0.18 parts of zirconium oxide.
[0039] in:
[0040] The chemical composition of the quartz sand is as follows in terms of mass percentage: SiO 2 99.57%,Al 2 O 3 0.21%, Fe 2 O3 0.0075% and loss on ignition is 0.2125%.
[0041] The chemical composition of the magnesia is as follows, in terms of mass percentage: MgO 97.85%, CaO 0.82%, SiO 2 0.43%, Fe 2 O 3 0.37%,Al 2 O 3 0.38% and loss on ignition is 0.15%.
[0042] The chemical composition of the calcined alumina is as follows, in terms of mass percentage: Al 2 O 3 99.72%, Na 2 O0.20%, loss on ignition is 0.08%.
[0043] The method for preparing the ultra-white glass described in this embodiment 2 comprises the following steps:
[0044] (1) Add quartz sand, sodium carbonate, colemanite, magnesia, calcined alumina, potassium oxide, zinc oxide and phosphorus pentoxide into a kiln for melting, vacuumize and degas for 8 minutes, then add strontium chloride, calcium fluoride, barium nitrate and zirconium oxide when the temperature reaches 580°C, continue to heat to 1530°C and keep the temperature for 8.2 hours to obtain glass liquid;
[0045] (2) The glass liquid is fed into a calender for calendering;
[0046] (3) The formed glass is annealed in an annealing kiln to produce ultra-white glass.
[0047] in:
[0048] The temperature of the calendering process in step (2) is 1150°C.
[0049] The annealing treatment in step (3) is to first cool the temperature to 520°C at a rate of 3.8°C / min and keep the temperature for 30 minutes, then cool the temperature to 320°C at a rate of 2.5°C / min, and finally cool naturally to room temperature. The whiteness of the ultra-white glass prepared in Example 2 is 0.066F, and the visible light transmittance is 94.7%.
[0050] Example 3
[0051] The ultra-white glass described in this Example 3 is composed of the following raw materials, in parts by weight: 110 parts of quartz sand, 18 parts of sodium carbonate, 16 parts of colemanite, 5.5 parts of magnesia, 2.6 parts of calcined alumina, 1.3 parts of potassium oxide, 0.8 parts of zinc oxide, 1.5 parts of phosphorus pentoxide, 0.20 parts of strontium chloride, 0.3 parts of calcium fluoride, 0.25 parts of barium nitrate, and 0.16 parts of zirconium oxide.
[0052] in:
[0053] The chemical composition of the quartz sand is as follows in terms of mass percentage: SiO 2 99.57%,Al 2 O 3 0.21%, Fe 2 O 3 0.0075% and loss on ignition is 0.2125%.
[0054] The chemical composition of the magnesia is as follows, in terms of mass percentage: MgO 97.85%, CaO 0.82%, SiO 2 0.43%, Fe 2 O 3 0.37%,Al 2 O 3 0.38% and loss on ignition is 0.15%.
[0055] The chemical composition of the calcined alumina is as follows, in terms of mass percentage: Al 2 O 3 99.72%, Na 2 O0.20%, loss on ignition is 0.08%.
[0056] The method for preparing the ultra-white glass described in this embodiment 3 comprises the following steps:
[0057] (1) Add quartz sand, sodium carbonate, colemanite, magnesia, calcined alumina, potassium oxide, zinc oxide and phosphorus pentoxide into a kiln for melting, vacuumize and degas for 10 minutes, then add strontium chloride, calcium fluoride, barium nitrate and zirconium oxide when the temperature reaches 600°C, continue to heat to 1550°C and keep the temperature for 8.3 hours to obtain glass liquid;
[0058] (2) The glass liquid is fed into a calender for calendering;
[0059] (3) The formed glass is annealed in an annealing kiln to produce ultra-white glass.
[0060] in:
[0061] The temperature of the calendering process in step (2) is 1180°C.
[0062] The annealing treatment in step (3) is to first cool the temperature to 530°C at a rate of 4.0°C / min and keep the temperature for 40 minutes, then cool the temperature to 330°C at a rate of 2.8°C / min, and finally cool naturally to room temperature. The whiteness of the ultra-white glass prepared in Example 3 is 0.064F, and the visible light transmittance is 95.3%.
[0063] Comparative Example 1
[0064] The preparation method of the ultra-white glass described in this comparative example 1 is the same as that of Example 1, the only difference being that the raw material composition is different. The ultra-white glass described in this comparative example 1 is composed of the following raw materials in parts by weight: 110 parts of quartz sand, 19 parts of sodium carbonate, 15 parts of colemanite, 5.0 parts of magnesia, 2.7 parts of calcined alumina, 1.2 parts of potassium oxide, 0.9 parts of zinc oxide, 1.6 parts of phosphorus pentoxide, 0.32 parts of calcium fluoride, 0.26 parts of barium nitrate, and 0.17 parts of zirconium oxide. The whiteness of the ultra-white glass prepared in comparative example 1 is 0.36F, and the visible light transmittance is 91.5%.
[0065] Comparative Example 2
[0066] The preparation method of the ultra-white glass described in this comparative example 2 is the same as that of Example 1, the only difference being that the raw material composition is different. The ultra-white glass described in this comparative example 2 is composed of the following raw materials in parts by weight: 110 parts of quartz sand, 19 parts of sodium carbonate, 15 parts of colemanite, 5.0 parts of magnesia, 2.7 parts of calcined alumina, 1.2 parts of potassium oxide, 0.9 parts of zinc oxide, 1.6 parts of phosphorus pentoxide, 0.18 parts of strontium chloride, 0.26 parts of barium nitrate, and 0.17 parts of zirconium oxide. The whiteness of the ultra-white glass prepared in comparative example 2 is 0.55F, and the visible light transmittance is 85.8%.
[0067] Comparative Example 3
[0068] The preparation method of the ultra-white glass described in this comparative example 3 is the same as that of Example 1, the only difference being that the raw material composition is different. The ultra-white glass described in this comparative example 3 is composed of the following raw materials in parts by weight: 110 parts of quartz sand, 19 parts of sodium carbonate, 15 parts of colemanite, 5.0 parts of magnesia, 2.7 parts of calcined alumina, 1.2 parts of potassium oxide, 0.9 parts of zinc oxide, 1.6 parts of phosphorus pentoxide, 0.18 parts of strontium chloride, 0.32 parts of calcium fluoride, and 0.17 parts of zirconium oxide. The whiteness of the ultra-white glass prepared in comparative example 3 is 0.41F, and the visible light transmittance is 88.4%.
[0069] Comparative Example 4
[0070] The preparation method of the ultra-white glass described in this comparative example 4 is the same as that of Example 1, the only difference being that the raw material composition is different. The ultra-white glass described in this comparative example 4 is composed of the following raw materials in parts by weight: 110 parts of quartz sand, 19 parts of sodium carbonate, 15 parts of colemanite, 5.0 parts of magnesia, 2.7 parts of calcined alumina, 1.2 parts of potassium oxide, 0.9 parts of zinc oxide, 1.6 parts of phosphorus pentoxide, 0.18 parts of strontium chloride, 0.32 parts of calcium fluoride, and 0.26 parts of barium nitrate. The whiteness of the ultra-white glass prepared in comparative example 4 is 0.23F, and the visible light transmittance is 92.2%.
Claims
1. An ultra-white glass, characterized in that: The invention is composed of the following raw materials in parts by weight: 110 parts of quartz sand, 18-20 parts of sodium carbonate, 14-16 parts of colemanite, 4.5-5.5 parts of magnesia, 2.6-2.8 parts of calcined alumina, 1.1-1.3 parts of potassium oxide, 0.8-1.0 parts of zinc oxide, 1.5-1.7 parts of phosphorus pentoxide, 0.15-0.20 parts of strontium chloride, 0.3-0.34 parts of calcium fluoride, 0.25-0.27 parts of barium nitrate and 0.16-0.18 parts of zirconium oxide.
2. The ultra-white glass according to claim 1, characterized in that: The chemical composition of the quartz sand, in terms of mass percentage, is as follows: SiO2 99.57%, Al2O3 0.21%, Fe2O3 0.0075%, and the loss on ignition is 0.2125%.
3. The ultra-white glass according to claim 1, characterized in that: The chemical composition of the magnesia is as follows, in terms of mass percentage: MgO 97.85%, CaO 0.82%, SiO2 0.43%, Fe2O3 0.37%, Al2O3 0.38%, and loss on ignition is 0.15%.
4. The ultra-white glass according to claim 1, characterized in that: The chemical composition of the calcined alumina, in terms of mass percentage, is as follows: Al2O3 99.72%, Na2O 0.20%, and loss on ignition 0.08%.
5. A method for preparing the ultra-white glass according to claim 1, characterized in that: It consists of the following steps: (1) Add quartz sand, sodium carbonate, colemanite, magnesia, calcined alumina, potassium oxide, zinc oxide and phosphorus pentoxide into a kiln for melting, vacuum and degas for 8-10 minutes, then add strontium chloride, calcium fluoride, barium nitrate and zirconium oxide when the temperature is raised to 580-600°C, continue to raise the temperature to 1530-1550°C and keep the temperature for 8.2-8.3 hours to obtain glass liquid; (2) The glass liquid is fed into a calender for calendering; (3) The formed glass is annealed in an annealing kiln to produce ultra-white glass.
6. The method for preparing ultra-white glass according to claim 5, characterized in that: The temperature of the calendering process in step (2) is 1150-1180°C.
7. The method for preparing ultra-white glass according to claim 5, characterized in that: The annealing treatment in step (3) is to first cool the temperature to 520-530°C at a rate of 3.8-4.0°C / min and keep it at that temperature for 30-40 minutes, then cool the temperature to 320-330°C at a rate of 2.5-2.8°C / min, and finally cool naturally to room temperature.
Citation Information
Patent Citations
Ultraviolet-resistant ultra-white rolled glass with high transmittance and production process
CN108516680A
Alkali-free aluminosilicate glass clarifying agent and preparation method of glass
CN113173702A